Route choice to inform navigation system design and accessibility analysis for older pedestrians: a scoping review - Fulman, Nir; Huber, Johannes; Lloyd, Armağan Teke; Foshag, Kathrin; Grinblat, Yulia; Türk, Umut; Lautenbach, Sven; Amcoff, Jan; Toger, Marina; Jokinen, Johanna; Zipf, Alexander (Journal of transport & health, 2025)
Introduction - Routing systems can support older adults by helping them overcome barriers to walking, promoting independence and well-being. The paths generated by these systems also inform urban accessibility metrics, such as those used in 15-min-city planning. Yet current systems rarely reflect the preferences or constraints of older pedestrians. Empirical studies of route choice can help close this gap by revealing how people trade off different route attributes in real settings. - Methods - We conducted a scoping review, following PRISMA-ScR guidelines, of empirical studies analyzing pedestrian route choice among adults. The goal was to identify findings that could inform the design of more age-inclusive routing tools. - Results - Eleven studies met the inclusion criteria, eight of which focused exclusively on older adults. Despite varied contexts, three consistent themes emerged: (i) sidewalk quality and manageable gradients; (ii) aesthetic and sensory comfort, including greenery, low noise, and good lighting; and (iii) access to benches, transit, and everyday amenities. However, most studies relied on qualitative methods, limiting direct integration into routing algorithms. - Conclusions - Future work should prioritize hybrid qualitative-quantitative designs, large-scale sampling of routes, and fine-grained mapping of micro-barriers. Analyses should account for age, gender, and functional ability, and consider circular leisure walks as a distinct travel pattern. These directions can enhance the usability and equity of routing systems and urban planning frameworks.
Online veröffentlicht: 12. August 2025
Gesehen am 18.08.2025